Mindfulness- A breakthrough in HIV treatment Significance of mindful practices in HIV treatment - Javed Iqbal, Dua; Seher, Muskan; Waseem, Radeyah (Journal of the Pakistan Medical Association, 2022)
HIV is a well-known cause of immunodeficiency as it suppresses the immune system leading to a plethora of symptoms collectively termed AIDS (Acquired Immunodeficiency Syndrome). Despite rigorous ongoing research and advancement in the associated risk factors of acquiring HIV, diagnosis, treatment, and prognosis, mortality reached the peak at 45% in 2015[1]. However, a recent study conducted in 2018 by Kate Hendricks Thomas et al. indicates that mindfulness practices enhance primary prevention practices and ameliorate the self-reported quality of life for patients suffering from chronic illnesses such as HIV and AIDS [2]. Mindfulness is described as complete awareness of our thoughts, bodily sensations, feelings, and the environment that surrounds us in a nurturing manner. Two specific types of mindfulness therapy are usually focused upon; Mindfulness-Based Cognitive Therapy (MBCT) and Mindfulness-Based Stress Reduction (MBSR). This could pave a new path towards efficiently countering the hindrances associated with the diagnosis and treatment of the disease in Pakistan. Pakistan is a high-risk country in terms of the prevalence of HIV[3], and it is high time to take drastic measures to restrict the spread and reduce the disease burden. Mindfulness-based therapies offer a potential solution here. Mindfulness-based stress reduction (MBSR) has also proven to improve neurocognitive performance, and psychosocial well-being, and reduce the harmful effects of stress that can increase viral replication, suppress the immune response, and hinder constancy to ART [4] [5]. Despite the surfacing positive factors, there is a scarcity of knowledge and awareness regarding mindfulness in Pakistan. The disease burden in Pakistan due to the stigmas and discrimination associated with the disease, reduced screening practices, and delayed ART regimens. Physicians here play a pivotal role in educating the masses about the above-listed obstacles, and also in educating and providing training regarding mindfulness practices. The government shares an equal responsibility to inform the public about mindfulness therapies and create opportunities for the public to indulge in this practice.